Is a cork a legal shortcut? - A comparison of the measured and assumed amount of rotation in freestyle tricks - Merz, C.; Naundorf, F.; Schüler, A.; Pickardt, S.; Gorges, T.; Supej, M.; Kersting, U. G. (Sports Biomechanics, 2025)
In snowboard freestyle disciplines, the amount of rotation is commonly determined as the sum of rotations around all board axes and is the most important indicator of the trick difficulty across all snowboard freestyle disciplines. Based on the type of rotation, tricks can be classified as flatspins, corks and flips. It is not yet known whether the type of rotation of a trick can influence the actual amount of rotation. Therefore, the aim of this study was to determine the amount of deviation, defined as difference between measured and assumed amount of rotation as a function of trick classification, using kinematic motion analysis. The amount of deviation was positive for flatspins (median: 21°; min: -4°; max: 49°) and negative for corks (median: -25°; min: -89°; max: 12°) and flips (median: -28°; min: -94°; max: 13°). Our results demonstrate that there are ways of execution where riders perform corks and flips with a shortcut and flatspins with a detour. This should be taken into account by judges, coaches and riders. Further research is needed to investigate how the shortcut can be influenced.